And i do not forgive you eaudiobook Stories and other revenges. - Sparks, Amber (HighBridge Audio, 2020)
Feminism fuels fantasy in this genre-busting collection by "master of the fantastic" (Roxane Gay) Amber Sparks. Exciting fans of such writers as Kelly Link, Karen Russell, and Carmen Maria Machado with prose that shimmers and stings, Amber Sparks holds a singular role in the canon of the weird. Now, she reaches new, uncanny heights with And I Do Not Forgive You. In "Mildly Happy, With Moments of Joy," a friend is ghosted by a simple text message; in "Everyone's a Winner at Meadow Park," a teen precariously coming of age in a trailer park befriends an actual ghost. At once humorous and unapologetically fierce, these stories shine an interrogating light on the adage that "history likes to lie about women"-as the subjects of "A Short and Speculative History of Lavoisier's Wife" and "You Won't Believe What Really Happened to the Sabine Women" (it's true, you won't) will attest. Blending fairy tales and myths with apocalyptic technologies, all tethered intricately by shades of rage, And I Do Not Forgive You offers a mosaic of an all-too-real world that fails to listen to its silenced goddesses.